An Investigation of the Effects of Manufacturing Parameters On Properties of Binderless Boards Produced from Abura (Mitragyna Ciliata) Sawdust - J. I., Orisaleye; A. A., Ogundare; Y. O., Abiodun; M. O., Oyekeye; O. A., Adefuye; S. J., Ojolo; O. E., Owoeye (International Journal of Integrated Engineering, 2023)
The production of particle boards without the use of synthetic binders is desirable to prevent environmental problems. This study has produced experimental binderless boards from untreated sawdust from Abura wood using a laboratory press. Box-Behnken experimental design was utilized to investigate the effects of the pressing variables including pressure, temperature and pressing time. The density of the boards produced ranged between 523.69 and 738 kg/m3 which was within the range specified for medium density fibreboards . The maximum values for Modulus of Elasticity (MOE), Modulus of Rupture (MOR) and Internal Bonding Strength (IB) were 100.4 MPa, 1.1 MPa and 0.049 MPa, respectively. It was shown that, for the range of factors studied, pressure and the pressing temperature were the more significant factors in determining the density, MOE and IB. This study showed that the sawdust can potentially be used for the production of binderless boards.